2019
DOI: 10.1136/archdischild-2019-317630
|View full text |Cite
|
Sign up to set email alerts
|

Using intermittent pulse oximetry to guide neonatal oxygen therapy in a low-resource context

Abstract: ObjectiveTo evaluate the effectiveness of intermittent pulse oximetry in guiding oxygen therapy in neonates in a low-resource setting.Design and settingProspective validation study at three hospitals in southwest Nigeria. We performed concealed continuous pulse oximetry on participants to evaluate intermittent SpO2 monitoring.PatientsWe recruited all preterm or low birthweight neonates, and all term neonates who required oxygen therapy, who were admitted to the neonatal ward(s) of the study hospitals during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(58 reference statements)
0
6
0
1
Order By: Relevance
“…The Nigeria Oxygen Implementation program implemented and evaluated improved oxygen systems in 12 secondary health facilities in south-west Nigeria. Results are published elsewhere [5,[16][17][18][19][20][21][22]. We found that the introduction of pulse oximetry and improved oxygen systems contributed to marked improvements in pulse oximetry and oxygen practices and was associated with reduced risk of death for children admitted with pneumonia, but not other illnesses [5].…”
Section: Introductionmentioning
confidence: 71%
“…The Nigeria Oxygen Implementation program implemented and evaluated improved oxygen systems in 12 secondary health facilities in south-west Nigeria. Results are published elsewhere [5,[16][17][18][19][20][21][22]. We found that the introduction of pulse oximetry and improved oxygen systems contributed to marked improvements in pulse oximetry and oxygen practices and was associated with reduced risk of death for children admitted with pneumonia, but not other illnesses [5].…”
Section: Introductionmentioning
confidence: 71%
“… 3 , 26 , 27 In the last 2-3 year however, routine screening is now taking place in some centers. 8 , 15 , 28 , 29 Though only 4 of the neonatologists that responded as shown in this paper were involved in ROP screening at the time of writing this article ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study looking at its use in low resource settings like Nigeria where it may not be available for each baby, it is advocated to at least monitor them more than 4.7 times a day to be able to better evenly maintain their SpO2. 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is encouraging to note that almost all neonates had continuous monitoring attached, with pulse oximetry being the most common modality. Pulse oximetry in particular plays an important role in avoiding the deleterious effects of hyperoxia, [15,16] such as retinopathy, bronchopulmonary dysplasia and complicating ductal-dependent CHDs. Vascular access and mechanical ventilation were also common attachments.…”
Section: Discussionmentioning
confidence: 99%